Analisis Prediksi Kebangkrutan Menggunakan Metode Altman Z-Score dan Zmijewski pada PT. Indofarma, Tbk - Lia Fitriani; Bella Puspita Rininda; Yuli Fitriyani; Maulida Hirdianti Bandi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to predict the potential bankruptcy of PT. Indofarma Tbk using the Altman Z-Score and Zmijewski (X-Score) methods. The data used in this study are the Annual Reports of PT. Indofarma Tbk listed on the Indonesia Stock Exchange. The method used in this research is descriptive quantitative analysis. The calculation and analysis of bankruptcy prediction using the Altman Z-Score method for PT. Indofarma Tbk from 2018 to 2022 show that the company is in an unhealthy condition or potentially bankrupt with Z-Score values of 1.50, 1.61, 1.32, 1.75, and -0.99, respectively. The calculation and analysis of bankruptcy prediction using the Zmijewski (X-Score) method for PT. Indofarma Tbk from 2018 to 2020 indicate that the company was in a healthy condition. In 2018, the X-Score was -0.46; in 2019, it was -0.71; and in 2020, it was -0.04. However, in 2021 and 2022, the X-Score calculations show the company was in an unhealthy condition or potentially bankrupt, with scores of 0.04 and 2.33, respectively. This research can serve as a reference for future researchers and as an evaluation material for the company to improve its financial performance.